Sosialisasi Anti-Plagiarisme dan Bijak Menggunakan Media Sosial bagi Mahasiswa Baru AKS Ibu Kartini Semarang - Esteria Priyanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
Socialization activities regarding anti-plagiarism and wisely usage of social media for new students are activities that are integrated in the Introduction to Campus Life for New Students (PKKMB) program in 2023. The aim of this socialization activities are to provide new students with new understanding and knowledge regarding anti-plagiarism and wise in using social media. The implementation stage of this socialization activities consists of 3 (three) stages, namely the preparation stage, implementation stage, and evaluation stage. The method used in this socialization activities are by providing information and presenting material for 1 (one) hour. The successful achievement of socialization activities for anti-plagiarism and wisely usage of social media was concluded through 2 (two) indicators, namely participant enthusiasm and participant ability in answering questions from the speaker. For the enthusiasm of the participants, all of them were very enthusiastic about the material provided. This was shown by all participants arriving on time and seriously following the socialization from the beginning until the end of proram. Regarding the participant's ability to answer questions from the speaker, all questions submitted by the speaker can be answered well and correctly by the participant.